The effect of soil moisture retention with amendment of superabsorbent polymer – review paper / Muhammad Alif Hafizuddin Rahmat - Rahmat, Muhammad Alif Hafizuddin (Faculty of Plantation and Agrotechnology, 2018)
The world now is facing the increasing of mean temperature. It was predicted that it keep increasing for another coming years. It is the most a biotic stress factor. These phenomena will affect a lot in agriculture sector as all type of soil will faced a huge problem that is loss moisture content. It will give impact to the growth of crop and their yield. In order faced the problem the usage of superabsorbent polymer as an amendment to the soil in order to improve the soil moisture retention in the soil. Superabsorbent polymer (SAP) is synthetic hydrophilic polymers that are in gel form. It has the ability to hold water or liquid in term of swelling much greater in term of their weight than the initial weight. Superabsorbent polymer has the ability to absorb high volume of water, 30 to 60 times its own volume. This review is to discuss about the effect of soil moisture content when amend by superabsorbent polymer in soil. The result shows that the SAP could improve soil moisture content and soil moisture retention and release it in time in soil and it could give significant impact to the soil although in low dosage especially in sandy type of soil.